2016
DOI: 10.1371/journal.pone.0168843
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Emotion in Parliamentary Debates with Automated Textual Analysis

Abstract: An impressive breadth of interdisciplinary research suggests that emotions have an influence on human behavior. Nonetheless, we still know very little about the emotional states of those actors whose daily decisions have a lasting impact on our societies: politicians in parliament. We address this question by making use of methods of natural language processing and a digitized corpus of text data spanning a century of parliamentary debates in the United Kingdom. We use this approach to examine changes in aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 48 publications
(36 reference statements)
5
90
1
Order By: Relevance
“…As studies in linguistics and psychology have shown, language can engender different emotions , and thereby influence the frame through which the world is perceived. By focusing on emotive language, our analysis contributes to an emerging literature looking at the use of emotion in political discourse (Rheault et al, 2016) and helps extend the study of manifestos beyond their traditional use as a means to examine issue salience and party positions (Breeze, 2011;Kosmidis et al, Forthcoming).…”
Section: Empirical Analysismentioning
confidence: 99%
“…As studies in linguistics and psychology have shown, language can engender different emotions , and thereby influence the frame through which the world is perceived. By focusing on emotive language, our analysis contributes to an emerging literature looking at the use of emotion in political discourse (Rheault et al, 2016) and helps extend the study of manifestos beyond their traditional use as a means to examine issue salience and party positions (Breeze, 2011;Kosmidis et al, Forthcoming).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Case study: a validation of the procedure with patterns of negativity in Austrian parliamentary speeches Sentiment analysis has increasingly turned to parliamentary debates as substantively interesting objects of study (e.g., Rheault, Beelen, Cochrane, & Hirst, 2016;Slapin & Proksch, 2014). A key component of what political opposition parties and their members do in parliaments of democratic systems is criticizing the government parties' policy ideas and the government ministers' work.…”
Section: Accuracy Measuresmentioning
confidence: 99%
“…The datasets were sourced from Irish and US Senate debates. Rheault et al (2016) examined the emotional polarity variations in speeches delivered in the British parliament over a hundred years. They observed a correlation between the variations in emotional states of a particular period of time and the national economic situation.…”
Section: Related Workmentioning
confidence: 99%